2020
DOI: 10.3390/su12177078
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Factors in Intergenerational Sustainability Dilemma: A Post-Interview Analysis

Abstract: An intergenerational sustainability dilemma (ISD) is a situation of whether or not a person sacrifices herself for future sustainability. However, little is known about what people consider while making a decision under ISD. This paper analyzes motivational factors for people to decide under ISD, hypothesizing that the factors can be different with or without perspective-taking of future generations. One-person basic ISD game (ISDG) along with post-interviews are instituted where a lineup of individuals is org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In summary, we have identified that FD has two features, i.e., its visioning practice and strategy-making process, which can be considered distinct from the practices and procedures of backcasting and scenario planning. Based on research and practice, FD mechanisms and practices are said to successfully induce people to be future-oriented and sustainable by triggering cognitive dissonance, empathy for future generations, expansions of their ways of thinking and paradoxical thinking [2][3][4][5][6][7][8][9][10]47,48]. Given this state of affairs, we suggest that linking and incorporating FD into some practices of backcasting and scenario planning are possible along with some potential benefits in that some important sustainable problems can be usefully analyzed [49].…”
Section: The Potential Benefits Of Linking and Incorporating Fd Into mentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, we have identified that FD has two features, i.e., its visioning practice and strategy-making process, which can be considered distinct from the practices and procedures of backcasting and scenario planning. Based on research and practice, FD mechanisms and practices are said to successfully induce people to be future-oriented and sustainable by triggering cognitive dissonance, empathy for future generations, expansions of their ways of thinking and paradoxical thinking [2][3][4][5][6][7][8][9][10]47,48]. Given this state of affairs, we suggest that linking and incorporating FD into some practices of backcasting and scenario planning are possible along with some potential benefits in that some important sustainable problems can be usefully analyzed [49].…”
Section: The Potential Benefits Of Linking and Incorporating Fd Into mentioning
confidence: 99%
“…Conversely, a future design (FD) approach has recently been advocated and researched. This approach can be considered a new element or member, potentially being linked to and incorporated into backcasting and scenario planning for sustainability [2][3][4][5][6][7][8][9][10]. This paper reviews some main features of the three approaches to future planning for sustainability and explores some possibilities of linking and incorporating FD into the existing approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that taking the perspective of future generations can affect how decision makers perceive the consequences of their own acts (e.g. climate change, Shahen et al, 2020). Concerning antibiotics, research suggests an association between physician’s empathy and prescribing behavior (Sun et al, 2017).…”
Section: Introductionmentioning
confidence: 99%